2012
DOI: 10.1186/1472-6920-12-110
|View full text |Cite
|
Sign up to set email alerts
|

Improving primary care in British Columbia, Canada: evaluation of a peer-to-peer continuing education program for family physicians

Abstract: BackgroundAn innovative program, the Practice Support Program (PSP), for full-service family physicians and their medical office assistants in primary care practices was recently introduced in British Columbia, Canada. The PSP was jointly approved by both government and physician groups, and is a dynamic, interactive, educational and supportive program that offers peer-to-peer training to physicians and their office staff. Topic areas range from clinical tools/skills to office management relevant to General Pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
16
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
9

Relationship

3
6

Authors

Journals

citations
Cited by 14 publications
(18 citation statements)
references
References 16 publications
1
16
0
1
Order By: Relevance
“…In BC, improvements to primary care involved first creating a partnership between government and physicians to take on leadership of improvement efforts. Policies to incentivize particular activities were matched by training opportunities to increase front-line capacities to reorient practice toward priority areas, and by the creation of regional Divisions of Family Practice as forums in which physicians could learn from each other and exchange ideas for improvement (128,129) .…”
Section: Discussion and Conclusion: The Politics Of Health System Redmentioning
confidence: 99%
“…In BC, improvements to primary care involved first creating a partnership between government and physicians to take on leadership of improvement efforts. Policies to incentivize particular activities were matched by training opportunities to increase front-line capacities to reorient practice toward priority areas, and by the creation of regional Divisions of Family Practice as forums in which physicians could learn from each other and exchange ideas for improvement (128,129) .…”
Section: Discussion and Conclusion: The Politics Of Health System Redmentioning
confidence: 99%
“…The PSP team was available to help support the physicians and medical office assistants in the implementation of the tools and the office redesign required. 12 The training usually took about five months to cover the three learning sessions and the two action periods that separated the learning sessions.…”
Section: Methodsmentioning
confidence: 99%
“…A novel continuing medical education (CME) program, the Practice Support Program (PSP) previously described by MacCarthy et al [ 1 , 2 ], continues to be offered to family physicians/general practitioners (GPs) and their staff in the province of British Columbia (BC), Canada. The PSP involves peer-to-peer training on a number of clinical and office management topics that are offered in learning modules for CME credit (see http://www.gpscbc.ca/practice-support-program ).…”
Section: Introductionmentioning
confidence: 99%
“…The PSP involves peer-to-peer training on a number of clinical and office management topics that are offered in learning modules for CME credit (see http://www.gpscbc.ca/practice-support-program ). MacCarthy et al [ 1 ] reported the results from the initial four PSP learning modules on chronic disease management, group medical visits, patient self-management, and advanced access/office efficiency, and MacCarthy et al [ 2 ] reported on the adult mental health module. Here we report the evaluation results from the PSP learning module that offers CME accredited training to GPs to enhance care for their patients who require end-of-life (EOL) care and their families.…”
Section: Introductionmentioning
confidence: 99%